Uschematyzowane wyglądy w teorii dzieła literackiego Romana Ingardena z perspektywy przekładu - Joanna Kubaszczyk (Ksiegarnia Akademicka Publishing, 2017)
Schematized Aspects in Roman Ingarden’s Theory of the Literary Work of Art From the Perspective of Translation In the article is considered if it is possible that there is some kind of representations similarity in case of the author of the Literary Work of Art and its readers and if an “imagination community” between readers of the original and the translation can be established. In the first part of the article the theory of Literary Work of Art by Ingarden is presented with a special focus on his “Schematized aspects”. Their function is to guarantee the vividness of the literary work. The types of vividness which are distinguish in the modern linguistics are told over as well. In the second part of the article the significance is emphasized to reconstruct the stratum of schematized aspects in the translation on the example of visual and auditory aspects and the relevance of the phenomenological theory of Literary Work of Art is pointed out both for translation theory and practice and for teaching of translating as well. The conclusion of the article is that the imagination community is possible because thanks to existence of schematized aspects in the literary work our representations – despite some differences in details – can have common elements if they are steered properly according to text instructions and if the reader self-disciplines his imagination to eliminate involuntary images. Whether the imagination community would be possible among recipients of the original and the translation depends extremely on the translator being able to reconstruct or to create analogous stratum of schematized aspects in the translation. The evidence that it is feasible are the congenial translations like Karl Dedecius’ translation of the poem W drodze by Stanisław Młodożeniec into German.